The democratisation of disempowerment the problem of democracy in the Third World - Hippler, Jochen (Transnational Institute series, 1995)
Thirteen authors explore key questions on Third World democratization. Examining local elites and social movements, violence and Western foreign policy, Islamic political movements and economic preconditions, the book concludes that democracy is not an easy commodity for export.